On the (Im)possibility of Withdrawing the Countersignature by the Prime Minister: A Few Remarks - Pałucki, Bartosz; Nieznański, Szymon (PRAWO i WIĘŹ, 2026)
Can a public authority retract its own decision? This question becomes crucial in the context of analyzing the institution of the counter-signature within the Polish constitutional system—particularly in light of attempts to withdraw the Prime Minister’s signature from an official act of the President of the Republic of Poland. The authors explore the permissibility of revoking a counter-signature, understood as an act of assuming political responsibility for the decision of the head of state. They argue that the counter-signature strengthens parliamentary oversight of the executive and constitutes an integral element of the constitutional procedure, whose legal effects are binding and durable. The analysis takes into account the systemic importance of the presumption of the counter-signature’s necessity and the strict interpretation of constitutional exceptions, leading to the conclusion that a unilateral withdrawal of responsibility for co-signed presidential acts is inadmissible.